2001
DOI: 10.2307/2696362
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Information in Health Insurance: Evidence from the National Medical Expenditure Survey

Abstract: Adverse selection is perceived to be a major source of market failure in insurance markets. There is little empirical evidence on the extent of the problem. We estimate a structural model of health insurance and health care choices using data on single individuals from the NMES. A robust prediction of adverse-selection models is that riskier types buy more coverage and, on average, end up using more care. We test for unobservables linking health insurance status and health care consumption. We find no evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
268
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(274 citation statements)
references
References 16 publications
5
268
0
1
Order By: Relevance
“…17 These are natural consequences of usage choices made under uncertainty about ex post marginal price. Hence the standard model (Cardon andHendel 2001, Reiss andWhite 2005), which assumes perfect consumer foresight, fits our data poorly. Now we turn to evidence that consumers are inattentive.…”
Section: Evidence For Stylized Factsmentioning
confidence: 68%
See 2 more Smart Citations
“…17 These are natural consequences of usage choices made under uncertainty about ex post marginal price. Hence the standard model (Cardon andHendel 2001, Reiss andWhite 2005), which assumes perfect consumer foresight, fits our data poorly. Now we turn to evidence that consumers are inattentive.…”
Section: Evidence For Stylized Factsmentioning
confidence: 68%
“…The standard approach to this problem assumes that consumers can forecast their usage perfectly, and so respond to the ex post marginal price (Cardon and Hendel 2001, Reiss and White 2005, Lambrecht et al 2007. A recent alternative relaxes perfect foresight but assumes consumers attentively track their usage from call to call (Yao et al 2012).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In most of these studies, moral hazard is ignored in order to focus on the identification of the two other sources of correlation between insurance and outcomes. (An exception to this is the paper on health insurance by Cardon and Hendel (2001).) Previous Australian studies looking at the effects of insurance on utilisation have generally found positive effects although the magnitudes vary a lot across studies.…”
Section: Background 21 Literature Reviewmentioning
confidence: 99%
“…Cardon and Hendel (2001), using data on single employed individuals (18 to 65 years old) from the National Medical Expenditure Survey (NMES), said no. So I don't lie awake nights, worrying about adverse selection for the bulk of the population.…”
Section: On Adverse Selectionmentioning
confidence: 99%